On the Performance of a Real‐Time Electron Radiation Belt Specification Model - Frances Staples; Adam Kellerman; Janet Green (Space Weather)
Abstract Maintaining accurate real‐time hindcast and forecast specification of the radiation environment is essential for operators to monitor and mitigate the effects of hazardous radiation on satellite components. The Radiation Belt Forecasting Model and Framework (RBFMF) provides real‐time forecasts and hindcasts of the electron radiation belt environment, which are used as inputs for the Satellite Charging Assessment Tool. We evaluated the long‐term statistical error and bias of the RBFMF by comparing the 10‐hr hindcast of electron phase space densities (PSD) to a multi‐mission data set of PSD observations. We found that, between the years 2016–2018, the RBFMF reproduced the radiation belt environment to within a factor of 1.5. While the error and bias of assimilated observations were found to influence the error and bias of the hindcast, data assimilation resulted in more accurate specification of the radiation belt state than real‐time Van Allen Probe observations alone. Furthermore, when real‐time Van Allen Probe observations were no longer available, the hindcast errors increased by an order of magnitude. This highlights two needs; (a) the development of physics‐based modeling incorporated into this framework, and (b) the need for real‐time observations which span the entire outer radiation belt.